Evaluación de los Parametros Fisicoquímicos en Reactores Discontinuos de Lodos Activados para el Tratamiento de Aguas con Metanol. - Carabali Lasso, Marvin; Lote Veloza, Martha Liliana; Echeverry Prieto, Lena Carolina (Ingeniería, 2017)
Context: There are currently several types of clean technologies aimed at decontamination of industrial waste water, such as activated sludge systems. These systems have proven effective in the removal of organic matter and colloidal in domestic wastewater and industrial, biosorption of heavy metals, and removal of pathogens and nutrients (N and P). The latter motivates the study of a controlled treatment system of activated sludge to scale, so as to demonstrate whether it can also be useful in industrial plants for treating water with methanol. Method: The treatment system of activated sludge was designed and built to scale in laboratory level to study different concentrations of methanol in waste water from one industry. We assembled five treatment systems and then measured physicochemical parameters as: pH, dissolved oxygen, temperature, chemical oxygen demand, total suspended solids, and loss of methanol. These measures were taken at 0, 24 and 48 hours by quadruplicate to observe the behaviour of the system in attempting the reduction of methanol. Results: The treatment system obtained an average loss of 10.3% methanol. On the other hand the average dissolved oxygen decreased in the time although chemical oxygen demand is variable. Each system with different concentration of methanol exhibits particular behaviour. Conclusions: This research suggests that biodegradation of methanol in waste water is possible, as it was shown in the controlled treatment systems. In addition, it indicates that further investigation on this type of clean technology is promising for the management of activated sludge for methanol removal at industrial scale.